The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1529-8817.2011.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

DIFFERENCES IN GROWTH AND PHYSIOLOGY OF MARINE SYNECHOCOCCUS (CYANOBACTERIA) ON NITRATE VERSUS AMMONIUM ARE NOT DETERMINED SOLELY BY NITROGEN SOURCE REDOX STATE1

Abstract: The preference of phytoplankton for ammonium over nitrate has traditionally been explained by the greater metabolic cost of reducing oxidized forms of nitrogen. This "metabolic cost hypothesis" implies that there should be a growth disadvantage on nitrate compared to ammonium or other forms of reduced nitrogen such as urea, especially when light limits growth, but in a variety of phytoplankton taxa, this predicted difference has not been observed. Our experiments with three strains of marine Synechococcus (WH7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Although the slower growth on nitrate could be explained by the greater amount of reducing power required to assimilate more oxidized N sources (García-Fernández et al, 2004), we assume that these cultures were growing at saturating light intensities based on previous measurements of light saturating irradiances for the growth of Prochlorococcus (Moore and Chisholm, 1999); thus energy supply and reducing power were likely not limiting. Furthermore, recent work has shown that the growth rates and chemical composition of some marine cyanobacteria are not directly related to the oxidation state of the cells' N source (Collier et al, 2012). Under light-limiting conditions, for example, the growth rate and chemical composition of Synechococcus grown on ammonium was the same as that on nitrate; however, under light-saturating conditions, cells grown on nitrate had a higher carbon-tonitrogen ratio (Collier et al, 2012).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the slower growth on nitrate could be explained by the greater amount of reducing power required to assimilate more oxidized N sources (García-Fernández et al, 2004), we assume that these cultures were growing at saturating light intensities based on previous measurements of light saturating irradiances for the growth of Prochlorococcus (Moore and Chisholm, 1999); thus energy supply and reducing power were likely not limiting. Furthermore, recent work has shown that the growth rates and chemical composition of some marine cyanobacteria are not directly related to the oxidation state of the cells' N source (Collier et al, 2012). Under light-limiting conditions, for example, the growth rate and chemical composition of Synechococcus grown on ammonium was the same as that on nitrate; however, under light-saturating conditions, cells grown on nitrate had a higher carbon-tonitrogen ratio (Collier et al, 2012).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, recent work has shown that the growth rates and chemical composition of some marine cyanobacteria are not directly related to the oxidation state of the cells' N source (Collier et al, 2012). Under light-limiting conditions, for example, the growth rate and chemical composition of Synechococcus grown on ammonium was the same as that on nitrate; however, under light-saturating conditions, cells grown on nitrate had a higher carbon-tonitrogen ratio (Collier et al, 2012). This perhaps suggests a bottleneck in the uptake and conversion of nitrate compared with ammonium when energy is sufficient (Collier et al, 2012), and may explain the In the early days of research on Prochlorococcus, the absence of cultures known to utilize nitrate resulted in a distorted view of the role of Prochlorococcus in marine ecosystems; ecosystem models and ecophysiological interpretations were guided by the assumption that most, if not all, Prochlorococcus were incapable of nitrate assimilation (García-Fernández et al, 2004;Fuller et al, 2005;Follows et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…However, despite expected energetic benefits of urea and NH 4 + , the wide variety of phytoplankton species response to different chemical forms of N (Fig. 3, 4) demonstrates that factors other than simple energetic costs of assimilation must also influence algal response to N, including temperature [20], [25], nutrient co-limitation [31], [37], or cellular stoichiometry [77], [87].…”
Section: Discussionmentioning
confidence: 99%
“…In steady or quasi‐steady‐state conditions, homeostatic mechanisms keep the acquisition of materials and energy in balance with the cellular growth demands. Consequently, when cells are grown under balanced growth conditions and comparable environmental conditions but under different N substrates, the differential—but acclimated—metabolism of NH4+ and NO3 generally leads to the same result: equivalent or nearly equivalent growth rates (e.g., Solomon et al ; Collier et al ; Collos and Harrison and references therein). If sufficient substrate is provided to saturate the growth demand (but not so high as to be growth suppressing), maximal growth rate is then defined by the ambient environmental conditions of growth (light, temperature, pH, etc.…”
Section: Coupling/uncoupling Of Uptake and Growth; C And N Homeostasismentioning
confidence: 99%